Design optimization and comparison of linear magnetic actuators under different topologies - Zhijian Ling; Jinghua Ji; Tao Zeng; Wenxiang Zhao (Chinese Journal of Electrical Engineering, 2020)
In this study, several types of linear actuators that adopt different permanent-magnet (PM) topologies are studied and compared. These linear actuators are based on the concept of PM magnetic screw transmission, which offers high force density, high reliability, and overload protection. Using different magnetic configurations and assembly methods, these linear actuators are designed and optimized for a fair comparison. Initially, based on the operating principle and maximum thrust force, the surface-mounted magnetic screw is described and optimized. Furthermore, the embedded magnetic screw, Halbach array magnetic screw, and field modulated magnetic screw are investigated and compared. Their electromagnetic performances, such as thrust force, torque, magnetic losses, and demagnetization effects are analytically assessed and verified using finite-element analysis. Finally, a prototype of the surface-mounted magnetic screw is developed to validate the predictions.